(untitled) (Development Engineering Conferences Center Articles Database, 2025)
Urate oxidase (Uricase), an important enzyme in the fields of industry and pharmaceuticals, plays a significant role in the conversion of uric acid to allantoin and the reduction of serum uric acid levels. This has led to increased interest among researchers in the stabilization of this enzyme. One effective method for stabilizing uricase involves the use of deep eutectic solvents (DES). In the present study, conducted at the Graduate University of Advanced Technology in Kerman, we cultured the BL21 bacteria and expressed and purified recombinant uricase. The impact of a glycerol-based eutectic solvent combined with the sugars fructose and sucrose on the enzyme’s kinetic parameters was examined. The results indicated that the eutectic solvent reduced the Michaelis constant (Km) and enhanced the catalytic efficiency of the enzyme in the presence of the eutectic compared to the free enzyme. This solvent, with its hydroxyl groups and influence on the enzyme’s intramolecular hydrogen bonds, significantly improved the enzyme’s kinetic stability.